Melanoleuca kashmirensis sp. nov. in subg. Urticocystis from Pakistan - Ullah, Zia; Khurshed, Rubab; Khan, Muhammad Binyamin; Ahmad, Israr; Jabeen, Sana; Faisal, Muhammad; Ahmad, Habib; Fiaz, Muhammad; Khalid, Abdul Nasir (Phytotaxa, 2020)
During this investigation, a new species of Melanoleuca subg. Urticocystis with urticiform cheilocystidia is proposed. The identification is based on morphological characters and molecular phylogenetic analyses using ITS and 28S sequences. A comparison of the morphological features and molecular phylogenetic data with the taxa of subg. Urticocystis confirms the identity of the species as a new taxon. The detailed descriptions, line drawings and phylogenetic results are given.